PVA Films with Mixed Silver Nanoparticles and Gold Nanostars for Intrinsic and Photothermal Antibacterial Action - Pietro Grisoli; Lorenzo De Vita; Chiara Milanese; Angelo Taglietti; Yuri Diaz Fernandez; Margaux Bouzin; Laura D’Alfonso; Laura Sironi; Silvia Rossi; Barbara Vigani; Paola Sperandeo; Alessandra Polissi; et al. (Nanomaterials, 2021)
PVA films with embedded either silver nanoparticles (AgNP), NIR-absorbing photothermal gold nanostars (GNS), or mixed AgNP+GNS were prepared in this research. The optimal conditions to obtain stable AgNP+GNS films with intact, long lasting photothermal GNS were obtained. These require coating of GNS with a thiolated polyethylene glycol (PEG) terminated with a carboxylic acid function, acting as reticulant in the film formation. In the mixed AgNP+GNS films, the total noble metal content is <0.15% w/w and in the Ag films < 0.025% w/w. The slow but prolonged Ag+ release from film-embedded AgNP (8–11% of total Ag released after 24 h, in the mixed films) results in a very strong microbicidal effect against planktonic Escherichia coli and Staphylococcus aureus bacterial strains (the release of Au from films is instead negligible). Beside this intrinsic effect, the mixed films also exert an on-demand, fast hyperthermal bactericidal action, switched on by NIR laser irradiation (800 nm, i.e., inside the biotransparent window) of the localized surface plasmon resonance (LSPR) absorption bands of GNS. Temperature increases of 30 °C are obtained using irradiances as low as 0.27 W/cm2. Moreover, 80–90% death on both strains was observed in bacteria in contact with the GNS-containing films, after 30 min of irradiation. Finally, the biocompatibility of all films was verified on human fibroblasts, finding negligible viability decrease in all cases.